Intensive Management of Post Caesarean Section with Eclampsia: A Case Report - Pratiaksa, Ardian; Eko Setijanto (HM Publisher, 2024)
Introduction: Eclampsia, a severe form of pre-eclampsia characterized by high blood pressure and seizures, poses a significant threat to both maternal and fetal health. With a global incidence of 2-8% among pregnancies affected by pre-eclampsia, eklampsia remains a leading cause of maternal mortality, particularly in low-resource settings. Given the potential for serious complications associated with postpartum eklampsia, it is crucial for anesthesia teams to possess a comprehensive understanding of the condition's management and the specific considerations required in the postpartum setting. Case presentation: We report a 19 years old woman post caesarean section with eclampsia. The patient had a recurrent seizure on the first day at the ICU. After had an intensive therapy at the ICU the patient showed a clinically improvement and extubated on the second day. The case highlights the importance of a holistic and comprehensive approach to postpartum care in eklampsia patients. By addressing not only the immediate symptoms but also the underlying physiological and neurological derangements, the ICU team was able to effectively manage the patient's condition and facilitate her recovery. Conclusion: Postpartum care in the intensive care unit needs to be hollistic and comprehensive with the aim of not aggravating the patient's condition and worsening the patient's prognosis.